International Law of the Sea in North Natuna Sea - Azhari, Yulian (Advances in Social Sciences Research Journal, 2020)
The dispute that occurred in the North Natuna Sea has attracted international attention, including the superpower United States of America and the People’s Republic of China and countries in the Southeast Asian region. This escalation of tensions occurred when the People’s Republic of China built military bases in areas considered the nine dash lines that the PRC claims as part of their country. International law continues to fail to enforce the North Natuna Sea. It is clear that international law has so far tried - and failed - to contain China’s advances in the North Natuna Sea. Existing confidence-building measures must match China’s increasingly hegemonic claims. If not, the rules-based order will face continued erosion and smaller countries in Southeast Asia will suffer the consequences. This study uses a qualitative approach with socio-historical analysis to reveal past events, especially in the field of maritime law, which are unknown to the international community.